Periodic Orbits of Radially Symmetric Keplerian-Like Systems with a Singularity - Shengjun Li; Yuming Zhu (Journal of Function Spaces)
We study planar radially symmetric Keplerian-like systems with repulsive singularities near the origin and with some semilinear growth near infinity. By the use of topological degree theory, we prove the existence of two distinct families of periodic orbits; one rotates around the origin with small angular momentum, and the other one rotates around the origin with both large angular momentum and large amplitude.